THE MENACE OF BANDITRY AND KIDNAPPING IN NIGERIA: AN ASSESSMENT OF SHEIKH GUMI'S MEDIATORY ROLE IN THE RELEASE OF GREENFIELD UNIVERSITY KIDNAPPED STUDENTS - SOLOMON AYANTAYO OJO; OLUSEGUN STEVE ADEGOKE (International Studies Journal)
The increase in banditry and kidnapping in Nigeria has created significant security challenges in recent years, particularly with attacks on educational institutions where students are abducted for ransom. Military and non-military strategies have been employed to address these problems but have not yielded the desired result, highlighting the potential of a mediation strategy. Studies on the menace of banditry and kidnapping in Nigeria are largely focused on their causes and sustenance, typology and military solution with less attention on mediation as a solution strategy. This study, therefore, examines the mediatory strategy employed by Sheikh Ahmed Gumi during the kidnapping of Greenfield University students. Utilising a qualitative research design, including case study and ex post facto methodologies, the findings indicate that Sheikh Gumi's mediation efforts played a crucial role in securing the release of the abducted students. The study also reveals that Gumi's informal mediation approach demonstrated elements of established mediation techniques including co-mediation, shuttle, and evaluative mediation. Consequently, the findings suggest that mediation can serve as an effective alternative strategy to address this security issue in Nigeria, and it recommended that the government promote such methods to combat banditry and foster peace and security in the nation.